Chemokines in Allergy - Chantry, D.; Burgess, L.E. (Current Drug Targets - Inflammation & Allergy, 2002)
Allergic diseases such as atopic dermatitis, asthma, and allergic rhinitis represent a significant healthcare problem. Understanding these diseases as dysregulated inflammatory responses has led to many new targets for therapeutic intervention. Recent data concerning soluble IL-4 receptor, monoclonal antibodies against IL-5 and an antibody toward IgE have lead to an appreciation of the crucial role played by Th2 subset of CD4 + T cells and their corresponding cytokines. While these potential drugs are presently in clinical trials and may be valuable therapeutics, orally bioavailable small molecule inhibitors of Th2 cell responses would be desirable for treatment of these chronic diseases. One strategy is to prevent effector cell migration (Th2 cells, mast cells, and eosinophils) via chemokine receptor antagonism with a suitable small molecule. Chemokine receptors are a subset of the seven transmembrane-spanning family, which mediate their effects through interaction with heterotrimeric G-proteins. The ligands are a structurally related set of proteins that are selectively expressed in certain disease settings. Three chemokine receptors CCR3, CCR4, and CCR8 are preferentially expressed by Th2 cells, mast cells and eosinophils and therefore represent therapeutic targets for allergy. This mini-review will focus on new research involving CCR3, CCR4 and CCR8. The cellular distribution of each receptor, the corresponding chemokine ligands, and various validation studies are discussed. Recent drug discovery advances concerning pharmacological tools and small molecule receptor antagonists will also be presented.
Keywords: ccr4